The Prevalence of Social Withdrawal in Infants With Cleft Lip and Palate: The Feasibility of the Full and the Modified Versions of the Alarm Distress Baby Scale - Pérez Martínez, Carla; Grollemund, Bruno; Gavelle, Pascale; Viaux-Savelon, Sylvie; Guedeney, Antoine (Frontiers in Pediatrics, 2022)
Background Social withdrawal is a risk indicator for infant development with both organic and non-organic causes. Cleft lip and palate (CLP) impose a higher risk of physical and emotional distress in infants and alters parent-infant relationships. The ADBB scale is a screening tool to identify social withdrawal as a sign of distress in infants. The aim of this study is to evaluate the prevalence of social withdrawal behavior in infants with CLP using the full 8-item ADBB scale and the modified 5-item ADBB scale, and to examine the feasibility of both scales. Methods 145 infants with Cleft Lip and Palate were enrolled and video recorded during a pediatric consultation. All infants were scored by two expert raters trained in ADBB scale, and subsequently scored with the m-ADBB by an independent expert. We measured the interrater agreement for the full ADBB scale and psychometric properties of both scales. Results The full ADBB scale identified 15.9% of infants as having social withdrawal behavior (score above cutoff ≥5). Among the infants evaluated with the m-ADBB scale, 44.9% had a score above the suggested cutoff (≥2). For both scales, the item “vocalization” showed the higher scores. We found a good internal consistency for the full ADBB (Cronbach's alpha = 0.82) and an acceptable internal consistency for the modified ADBB (Cronbach's alpha = 0.71). The interrater agreement for the full ADBB scale was excellent (kappa = 0.837). The Spearman correlation coefficient between the total scores of the two versions was 0.88 (P < 0.001). Conclusion Our results indicate a relatively high prevalence of social withdrawal in infants with Cleft Lip and Palate, especially evaluated with the modified 5-item ADBB scale. We found that the full ADBB and the modified ADBB scales are feasible to use as screening tools of social withdrawal in this population. Clinical Trial Registration This trial is registered on ClinicalTrials.gov, identifier: NCT00993993. The data is the property of Assistance Publique, Hôpitaux de Paris.